Chronic oral anticoagluation and risk of prostate cancer: Evidence of detection bias. Issue 11 (23rd October 2019) - Ward, Michael M.
Abstract : Warfarin treatment has been associated with lower risks of prostate cancer, without a specified biological mechanism. Our study tested the hypothesis that reluctance to perform prostate biopsies in men who are anticoagulated results in lower rates of diagnosed prostate cancer, leading to an apparent protective effect. Rates of prostate biopsies have decreased from 2000 to 2015, allowing calendar time to be used as the intervention. In a national population‐based sample of elderly men, our study compared trends in prostate cancer incidence between 17, 815 men treated with chronic oral anticoagulation for prosthetic heart valve thromboprophylaxis and a general population comparison group of 356, 300 men. Cancer events were based on administrative claims. Among men enrolled in 2000–2001 and followed through 2015, prostate cancer incidence was substantially lower in the anticoagulation group (adjusted incidence rate ratio [IRR] 0.70; 95% confidence interval [CI] 0.62–0.80). Incidence decreased over time in the general population group to approach that of the anticoagulation group among men enrolled in 2008–2010 (IRR 0.86; 95% CI 0.71–1.04). Rates of prostate biopsies also decreased over time in the general population group to match the rate in the anticoagulation group. These results indicate that the apparent protective effect of warfarin treatment on the risk of prostate cancer is likely the result of detection bias from lower rates of biopsies among men who are anticoagulated. Abstract : What's new? Warfarin treatment has been associated with lower risks of prostate cancer, without a specified biological mechanism. However, reluctance to perform prostate biopsies in men who are anticoagulated could result in underdiagnosis. This national population‐based study of elderly men compared trends in prostate cancer incidence between 17, 815 men treated with chronic oral anticoagulation for prosthetic heart valve thromboprophylaxis and a general population comparison group of 356, 300 men. These results indicate that the apparent protective effect of warfarin treatment on the risk of prostate cancer is likely the result of detection bias from lower rates of biopsies among men who are anticoagulated.